Selection of acid compositions in well construction in difficult geological conditions; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Mishchenko M. V. Maria Valerievna (Well drilling, 2016)
Title screen